Knitting Peter Rabbit : 12 toy knitting patterns from the tales of Beatrix Potter - Garland, Claire (David & Charles, 2023)
"With step-by-step instructions and beautiful photography, you'll be able to make all the most enduring characters from Beatrix Potter's world. Knit Peter Rabbit, Benjamin Bunny, Flopsy Bunny, Jemima Puddle-Duck, Mrs. Tiggy-Winkle, Mr. Jeremy Fisher, Tom Kitten, Squirrel Nutkin, the Tailor of Gloucester, Samuel Whiskers, Mr. Tod the fox, and Tommy Brock the badger, and dress them up in simple felt garments to complete the storybook look"--Publisher's description.